Mechanical Properties and Microscopic Mechanisms of Expansive Soil under the Action of Acid and Alkali Solutions - HU Bo, LI Wei, MA Kun, YUAN Rui-xiang, WANG Shuai, SUN Hui (长江科学院院报)
[Objective] The aim of this study is to investigate the effects of acid-base conditions on the mechanical properties of expansive soil. [Methods] Expansive soil from Section C003 of the Yangtze-to-Huaihe Water Diversion Project was taken as the research object. A self-developed leaching test device was employed to leach expansive soil samples with acid-base solutions of varying pH values. After leaching, the relationship between strength changes of expansive soil and pH values of solutions was investigated using critical water content tests and consolidated drained triaxial shear tests. Chemical composition analysis and X-ray diffraction tests were conducted to investigate the underlying mechanism driving the variations in physical and mechanical properties. [Results] (1) After 7-day leaching with acid and alkali solutions, the samples showed different changes in morphology and form. Specifically, during acidic solution leaching, microbubbles formed on the sample surface, which developed into numerous pores after 7 days of leaching. In contrast, during alkaline solution leaching, no significant surface changes were observed initially, but after 7 days of leaching, the samples exhibited volume expansion and white crystals formed on the surface. (2) Critical water content and triaxial compression tests revealed that after 7 days of acidic solution leaching, the physical and mechanical properties of expansive soil blocks progressively deteriorated with decreasing pH values (compared to samples leached with pH=7 solution). Specifically, as pH values decreased, the liquid limit, plastic limit, and plasticity index decreased, the cohesion showed a significant decrease, and the internal friction angle showed a minor decrease. After 7 days of alkaline solution leaching, the physical and mechanical properties of expansive soil blocks gradually strengthened with increasing pH values (compared to samples leached with pH=7 solution). Specifically, as pH values increased, the liquid limit, plastic limit, and plasticity index increased, the cohesion showed a significant increase, and the internal friction angle showed a slight increase. (3) XRD tests and chemical composition analysis of expansive soil blocks after acid and alkali solution leaching revealed that the interaction mechanisms between the acid and alkali solutions and the soil primarily involved ion exchange and reactions between soil minerals and solutions. These processes modified the double-layer thickness between soil particles and the content of free oxide cements and water-soluble salts, thereby changing the interparticle contact patterns and soil microstructure. After acidic solution treatment, the diffuse double-layer became thinner, the cements were dissolved, and the soil structure deteriorated, leading to progressively deteriorating physical and mechanical properties with decreasing pH. After alkaline solution treatment, the diffuse double-layer became thicker, accompanied by the formation of new cements that filled pores of various sizes inside the soil, making the soil structure more compact, leading to systematically enhanced physical and mechanical properties with increasing pH.